Echa socjalizacji medialnej. Frazemy telepochodne w wypowiedziach dzieci - Emilia Kałuzińska (Postscriptum Polonistyczne)
In many children’s statements there are expressions that are uncharacteristic for the age of the speakers. Such expressions often turn out to be inspired by television. The aim of the article is to select such expressions, that have been described here as „TVinspired phrasems”. They are then analysed using the tools created by Wojciech Chlebda. These analysed expressions have been found in linguistic publications, on TV and radio programs. They are analysed in relation to their sociological context (media socialization, concept of homo videns by Sartori).